“All flat maps, and I am one”: Cartographic References in the Poems of John Donne - Ladan Niayesh (Etudes Epistémè)
Drawing both on the medieval Mappae mundi and the Ptolemaic tradition revived in the Renaissance, the recurrent cartographic motif in John Donne’s poetry well reflects the preoccupations of a revolutionary period in the history of Western cartography. Yet, for all its cosmic magnitude, Donne’s poems, both holy and secular, are turned, not so much towards an exploration of the world as towards an exploration of the Self as the ultimate object of reflection.